Transoral endoscopic thyroidectomy for papillary thyroid microcarcinoma: initial experience of a single surgeon - Chai, Young Jun (Ann Surg Treat Res, 2017)
PURPOSE: Recently, transoral endoscopic thyroidectomy (TOET) is receiving attention because it is regarded as a true minimally invasive surgery in that it does not leave scars on any part of the body and the area of flap dissection is similar to that of open surgery. In this study, we present the surgical procedures and initial outcomes of TOET in the treatment of papillary thyroid microcarcinoma (PTMC) patients. METHODS: The medical records of patients who underwent TOET for PTMC between July 2016 and February 2017 were retrospectively reviewed. Indication of TOET was PTMC without capsular invasion or lymph node metastasis on preoperative imaging studies. RESULTS: Ten female patients were enrolled. Seven patients underwent thyroid lobectomy and three patients underwent isthmusectomy. The mean age and tumor size was 43.3 ± 11.5 years and 0.6 ± 0.2 cm, respectively. Operation time for lobectomy and isthmusectomy was 121.1 ± 30.7 (range, 65–148) and 90.0 ± 9.2 minutes (range, 82–100 minutes), respectively. The mean number of retrieved lymph nodes was 2.7 ± 1.7. Two patients had transient vocal cord palsy, which recovered in three months. There was no case with subcutaneous emphysema, surgical site infection, postoperative bleeding, or mental nerve injury. CONCLUSION: TOET was feasible and could be performed safely for PTMC. TOET might become a new treatment option for the patients who do not want to leave visible scars on the body.